Maxillaria tenebrosa, a new species in the Maxillaria variabilis group (Orchidaceae: Maxillariinae) from Southwestern Ecuador - Romero, Bosco Javier Zambrano; Solano-Gomez, Rodolfo (Phytotaxa, 2016)
Maxillaria tenebrosa, a new species discovered in Southwestern Ecuador is described and illustrated. Information concerning its distribution, habitat, floral biology, and conservation status is provided. The new taxon is a member of M. variabilis group or M. section Erectae, and it is compared with morphologically similar species such as M. acervata, M. caespitifica, M. caucae, M. costaricensis, M. dichaeoides, M. ponerantha, M. procurrens, M. variabilis, and M. xanthorhoda.